Analisis Kinerja Tenaga Administrasi Sekolah dalam Layanan Kependidikan di Sekolah Menengah Pertama Negeri 4 Talang Kelapa Kabubaten Banyuasin - Kurniati, Meriza; Mardianto, Mardianto; Hestirinaih, Deby Chintia (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
This research shows that: overall the performance of school administrative staff in educational services at Talang Kelapa 4 State Junior High School, Banyuasin Regency has been well implemented, although there are still obstacles in its implementation, including: School administration staff is still lacking and facilities in implementing educational services are still lacking adequate. The indicators that have been implemented properly are accuracy, neatness, work speed of each employee, level of employee knowledge about work, employee obedience to work, employee ability to work together with others, employee ability to adapt to the environment, employee thinking and creativity , Ability to submit new ideas/proposals. While what has not been implemented properly is the ability of employees to adapt to work and the ability of employees to complete tasks / jobs.